Ensino de Tato para Crianças com Transtorno do Espectro Autista com Estímulos Discriminativos Mais Preferíveis e Menos Preferíveis - Amanda Carolina Botareli Cesar (2024)
This study aims to evaluate the tact verbal operant learning in children diagnosed with Autistic Spectrum Disorder (ASD), comparing two teaching methods after preferred items assessment. One of the methods applied discriminative stimuli with most preferred items, while the other one used less preferred items as stimuli. The diagnostic criteria for the spectrum are included, as outlined in the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), emphasizing the persistent deficits in social communication. Verbal behaviors were classified based on verbal operant definitions, more specifically, tact, which is the focus of this study. Tact is defined by Skinner as the verbal operant which response is controlled by a prior nonverbal stimulus (such as an object, event, or property), and this response is maintained by nonspecific social reinforcement. For the single-case experimental design, the subjects were 3 children with ASD between 6 and 7 years old, who have each been through the procedure for teaching tacting, one at a time. During the training, reinforcing stimuli selected by the participants were applied, as well as less reinforcing stimuli selected by the experimenter. This research presents the tact training results, comparing both teaching strategies adopted.